2018
DOI: 10.1093/cid/ciy233
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in All-Cause Acute Otitis Media in Children <3 Years of Age in Primary Care Following Vaccination With 10-Valent Pneumococcal Haemophilus influenzae Protein-D Conjugate Vaccine: A Whole-Population Study

Abstract: The impact of PHiD-CV10 on all-cause AOM was considerable, mediated mainly by preventing the first two episodes of AOM. A decrease in the IR of AOM in children too young to receive direct vaccine protection was demonstrated, suggesting herd effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…15,16 Many studies have shown that PCVs reduce AOM episodes, especially "severe" cases, and that this is mainly due to decreased incidence of pneumococcal AOM. 11,12,14,23 In a study conducted in Athens, Greece, Stamboulidis et al 15 found similar percentages of S. pyogenes (29%) in MEF cultures to us in children with AOM complicated by otorrhea after the introduction of PCV7. There are other analyses of MEF microbiology that also found remarkable prevalence of S. pyogenes and S. aureus in the postvaccine period.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…15,16 Many studies have shown that PCVs reduce AOM episodes, especially "severe" cases, and that this is mainly due to decreased incidence of pneumococcal AOM. 11,12,14,23 In a study conducted in Athens, Greece, Stamboulidis et al 15 found similar percentages of S. pyogenes (29%) in MEF cultures to us in children with AOM complicated by otorrhea after the introduction of PCV7. There are other analyses of MEF microbiology that also found remarkable prevalence of S. pyogenes and S. aureus in the postvaccine period.…”
Section: Discussionsupporting
confidence: 55%
“…Widespread adoption of the PCVs has led to a dramatic decrease in the incidence of invasive pneumococcal disease in children 7,8 and to a modest reduction in the incidence of AOM. [9][10][11][12] Both the introduction of PCVs and antibiotic selective pressure have resulted in changes in distribution of the bacterial causes of AOM over time. [13][14][15][16] For AOM, pneumococci and H. influenzae are the main targets of antibiotic prescription.…”
Section: Introductionmentioning
confidence: 99%
“…Children in the vaccine-eligible cohorts who underwent the procedure had visited a physician less often for the treatment of otitis media and had filled antimicrobial prescriptions than children in the VNEC, before undergoing the procedure. The largest increase in the incidence of TTP was observed in children 12-17 and 18-23 months of age, despite a considerable reduction in the incidence of acute otitis media in those age groups (10). These results are unexpected.…”
Section: Discussionmentioning
confidence: 84%
“…Even if it were the case, there is evidence to suggest that PCV decreases both recurrent acute otitis media and serous otitis media (8,29). This study group has previously shown that recurrent acute otitis media has decreased in Iceland following the introduction of PHiD-CV10 (10). There is an increasing trend in the incidence of TTP in the vaccine non-eligible cohorts among children 12-17 and 18-23 months of age, as seen in Figure 1.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation